The Impact of Rural Fires on the Development of Invasive Species: Analysis of a Case Study with Acacia dealbata Link. in Casal do Rei (Seia, Portugal) - Nunes, Leonel (2022)
Biological invasions can affect ecosystems in different ways. Invasive forest species, such as Acacia dealbata Link., affect forests’ productivity, because they compete directly with native species for access to light and nutrients, contributing to the loss of biodiversity. In this study, an area occupied by A. dealbata, located in Casal do Rei (Seia, Portugal) was studied to evaluate the influence of fire in the dispersion of this species, analyzing the historical occurrence of rural fires in the region, as well as through the determination of its annual biomass production and comparing its growth with other species using satellite images. The research shows a competitive advantage for A. dealbata, even when compared to species, such as Eucalyptus globulus and Pinus pinaster, which practically disappeared from the location under study after a significant fire occurred in 2005, while A. dealbata continued to thrive.